Czynniki konkurencyjności polskiego sektora MSP w latach 2001-2007 - Duda, Joanna (Competitiveness of the Polish Sme Sector Between 2001 and 2007, 2008)
The competitiveness of the Polish SME sector became the subject of many scientific disputes, especially in the aspect of Poland's accession to the EU. The entrepreneurs encountered and still encounter many barriers limiting the increase of their competitiveness level. Because of this they compete mainly on price, while the other factors like: quality or uniqueness of their services and goods play a lesser role. The fact that more than half of entrepreneurs did not make any investments decisions is bothering, nevertheless interest of entrepreneurs in R+D and environmental investments seems to be a positive change. The observations above induced the author to provide in this paper the analysis of competitiveness barriers and factors of the Polish SME sector between 2001 and 2007.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 144-152